2021
DOI: 10.3897/folmed.63.e55911
|View full text |Cite
|
Sign up to set email alerts
|

Initial experience in the field of pediatric percutaneous nephrolitholapaxia in Bulgaria

Abstract: Introduction: Pediatric urolithiasis is a very specific and challenging problem in the field of modern urology. Currently, there are three major methods for kidney stone removal: the extracorporeal shock wave lithotripsy (ESWL), the retrograde intrarenal surgery (RIRS), and the percutaneous nephrolithotomy (PCNL), the latter one proving to be an efficient and safe monotherapy of stones even with larger burden. Different sizes of nephroscopes are used (standard, mini, micro), where smaller size is logically cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Two recent studies have also confirmed mini PCNL's efficacy and safety to be done towards children with urinary tract stones. [34][35] This study was a pilot meta-analysis on the efficacy and safety of mini PCNL for pediatric nephrolithiasis. A limitation of this study is that it lacked sufficient resources, including only two studies for all quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Two recent studies have also confirmed mini PCNL's efficacy and safety to be done towards children with urinary tract stones. [34][35] This study was a pilot meta-analysis on the efficacy and safety of mini PCNL for pediatric nephrolithiasis. A limitation of this study is that it lacked sufficient resources, including only two studies for all quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%